2018
DOI: 10.1002/asjc.1808
|View full text |Cite
|
Sign up to set email alerts
|

Reduced‐order Observer for State‐dependent Coefficient Factorized Nonlinear Systems

Abstract: This paper presents a reduced-order observer for state-dependent coefficient factorized nonlinear systems. By considering that a partial knowledge of the state vector is available from measurements, estimating the full state vector may be unnecessary, which consequently reduces the order of the observer and thus avoids unnecessary implementation issues. In this manuscript, the asymptotic convergence of the proposed reduced-order observer is established when an adequate state-dependent factorization for the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…To compare the proposed controller against existing ones, Table 3, displays the mean value and standard deviation for speed tracking error, to a comparison between an optimal tracking control (OTC) [29], a conventional discrete-time sliding mode control (SMC) scheme [30], a NIOC with a neural observer (NIOCNO) [22] with respect to the proposed Quantized NIOC. It is shown that the proposed Quantized NIOC presents the best performance.…”
Section: Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the proposed controller against existing ones, Table 3, displays the mean value and standard deviation for speed tracking error, to a comparison between an optimal tracking control (OTC) [29], a conventional discrete-time sliding mode control (SMC) scheme [30], a NIOC with a neural observer (NIOCNO) [22] with respect to the proposed Quantized NIOC. It is shown that the proposed Quantized NIOC presents the best performance.…”
Section: Comparative Analysismentioning
confidence: 99%
“…OTC [29] 0.027393 0.04821 SMC [30] 0.008358 0.09212 NIOCNO [22] 0.002468 0.04703 NIOC 0.001023 0.00763…”
Section: Controller Mean Value (M/s) Standard Deviation (M/s)mentioning
confidence: 99%
“…Theorem 3.1. Consider the conformable fractional-order system (2) in its healthy operating case (f = 0), under assumption 1 and the observer (5). If there exist matrices X and P = P T > 0 and positive scalars β and η such that the condition (7) is feasible, then the error origin e = 0 is globally fractional exponential stable.…”
Section: The Healthy Operating Casementioning
confidence: 99%
“…To summarize the previous discussion in this section, conditions that allow the system states in the healthy operating case, as well as in the faulty operating cases, to be accurately reconstructed have been validated for this numerical example. Now, one can exploit the observers (5) and (10) and present the simulation results. The initial conditions and the fractional derivative order are chosen as:…”
Section: Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation